Analyzing The Challenges and Opportunities Related to Biomedical Waste Management in District-Level Hospitals - Amin, Md Nurul; Hassan, Parvez; Islam, SM Shahinul (Journal of Rangpur Medical College, 2026)
Background: Effective biomedical waste management is crucial for safeguarding healthcare personnel, patients, and the environment from the dangers posed by toxic hospital waste. District-level hospitals in Bangladesh continue to have difficulties in establishing efficient waste management systems. Objective: This study aimed to examine the difficulties and opportunities associated with biomedical waste management practices among healthcare professionals in designated district-level hospitals in Bangladesh. Methods: A descriptive cross-sectional study was performed from March 2025 to November 2025 in designated district-level hospitals in Bangladesh. A total of 130 healthcare practitioners, encompassing physicians, nurses, custodians, and administrators, engaged in the study. Data were gathered through structured questionnaires and analysed using SPSS version 26. Descriptive statistics, including frequencies, percentages, means, and standard deviations, were employed. Results: A moderate level of awareness of biomedical waste management among healthcare professionals was observed. Approximately 73.1% were cognizant of BWM regulations, and 60% had undergone training. Nonetheless, fewer than 50% continuously implemented waste segregation at the source. Incineration (26.9%) was the predominant treatment modality. Significant issues comprised insufficient staff awareness or training (26.9%), poor infrastructure (23.1%), and deficient monitoring (19.2%). Participants recommended consistent training, enhanced infrastructure, sufficient PPE provision, and increased oversight to improve biomedical waste management methods in hospitals. Conclusion: Results from this study suggested enchaining training, infrastructure, and proper supervision is essential to improve biomedical waste management in district levels hospitals to mitigate the health and environmental hazards in Bangladesh. J Rang Med Col.2026 Mar;11(1): 92-98